Kh. Sahal Mahfudz Sebagai Musnid Nusantara: Pelestarian Hadis Dan Penguatan Sanad Di Tengah Tantangan Sosial Modern - Zaimuddin; Muhammad Khoirur Roziqin (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study examines the role of KH. MA. Sahal Mahfudz in preserving and strengthening the hadith tradition in Indonesia, focusing on two main aspects: (1) his contributions to tahammul (reception), ada’ (transmission), and kitabah (writing) of hadith, demonstrating his dedication to maintaining the authenticity of the sanad; and (2) his potential as a musnid of Indonesia, serving as a pivotal figure in the narration and sanad of hadith in the Nusantara, thereby enhancing Indonesia’s position in the global hadith tradition through his connections with prominent scholars like Syaikh Muhammad Yasin al-Fadani. Employing a qualitative approach based on literature analysis, this study explores KH. Sahal’s biography, scholarly capacity, and works, particularly Lum‘at al-Himmah ilā al-Musalsalāt al-Muhimmah. The findings reveal that KH. Sahal not only preserved the continuity of hadith sanad but also integrated hadith with social fiqh as a contextual hermeneutical framework, making hadith relevant to modern challenges such as social injustice and community empowerment. This research enriches the discourse on Islamic scholarship in the Nusantara by affirming KH. Sahal’s role as a multidimensional figure who combined the hadith tradition with social sensitivity, while recommending the strengthening of hadith curricula in pesantren and academic collaborations to promote Indonesia’s sanad internationally.